Unraveling the Underwater Morphological Features of Roncador Bank, Archipelago of San Andres, Providencia and Santa Catalina (Colombian Caribbean) - Idárraga-García, Javier; León, Hermann (Frontiers in Marine Science, 2019)
In this study we present the first detailed description of the morphology of the Roncador Bank deep underwater environments, located in the central sector of the SeaFlower Biosphere Reserve (Archipelago of San Andres, Providencia and Santa Catalina-ASAPSC, Republic of Colombia). The analysis was carried out from multibeam bathymetric information recently acquired by the Oceanographic and Hydrographic Research Center of Colombia (CIOH), and the subsequent creation of a 35 m-resolution digital terrain model, which was the main input for the geomorphological mapping. The results allowed to determine that Roncador Bank corresponds to a seamount of highly irregular contour, reaching a height up to 2350 m with respect to the surrounding seafloor. The volcanic edifice that makes up the seamount is bounded to the south and east by two escarpments, which are tectonically related with the Southern Roncador and Eastern Roncador faults, respectively. We were able to determine that these faults are currently active and that recently have generated earthquakes of magnitudes up to 6.0, which has important implications for the estimated seismic risk in the ASAPSC. This situation allowed to infer that the volcanic processes that formed the Roncador volcano were controlled by the presence of major faults on the seabed. The steep slope gradients (up to 40°) of the escarpments effectively concentrate erosive processes, leading to the development of a dense gully network and extensive slope deposits in the hillsides. Also, we identified debris-avalanche deposits indicating the occurrence of partial collapses of Roncador, which shows that gravity-driven mass transport processes have played an important role in the edifice shaping. These large-scale underwater landslide events may have the capacity to generate tsunamis, so it is necessary to carry out specific studies to analyze their tsunamigenic potential. Finally, the mapping and detailed description of Roncador seamount morphological features, such as pinnacles, escarpments, hummocky terrains, ridges, gullies and canyons, reported in this study are key to advance in the basic knowledge on the geology and geomorphology of the ASAPSC, and have direct implications for future specific research on the characterization of deep ecosystems, geohazards, natural resources, and territory planning